DFIG wind-turbine modeling with reactive power control integrated to large distribution network - Banawair K.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
The growth rate of penetration of wind energy has addressed many challenges and impacts related to the power quality and power system stability because of its intermittent nature. Once a doubly fed induction generator (DFIG) is connected to a power system, it absorbs lagging reactive power during the grid operation causing instability issues to the grid voltages. In this research paper, a DFIG based wind turbine is being modeled considering the optimal power coefficient and reactive power control strategy. The optimal power coefficient correlates the power law exponent with the respect of velocity and elevation. The reactive power control strategy is modeled using back-to-back converter system. The paper also investigates the voltage improvement of a large distribution network connected with DFIG system. By using steady state analysis, the voltage magnitude profiles are determined during DFIG at point of common coupling. The proposed control shows that DFIG based wind-turbine integration to the large distribution network enhances the weak bus voltage. © 2014 IEEE.